Exploring Miscommunications in the Construction Industry Through Experiments - Shreya Koirala; Endong Wang; Aidan Ackerman; Seyeon Lee (Engineering Proceedings)
Through a formal experiment, this study aims to identify miscommunication scenarios, quantify miscommunication levels, and analyze potential factors influencing communication in the construction industry with a focus on the communications between owners and designers. The study entails a five-step process: literature review, experiment design, questionnaire formulation, experiment execution, and post-experiment survey. Data analysis indicates that the owners and designers interpreted the communication processes and contents differently, with the presence of communication barriers leading to misunderstandings, errors, and misinterpretation of the design ideas. The utmost need is identified for improved communication strategies within design and construction projects to minimize miscommunications and support project success.